ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (STUDI PADA PELANGGAN KANTOR POS PURWOREJO) - Agustyn, Renata Riskia; Santosa, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2013)
This research is motivated by the increasing number of mail delivery services and goods and the growing sophistication of technology. While the selected object in this study is customer of Purworejo Post Office where a decline in the level of customer arrivals Purworejo Post Office and the increasing number of complaints. Purpose of this study was to determine the effect of tangible, reliability, responsiveness, assurance, and empathy towards customer satisfaction Purworejo PostOffice.After a literature review and compose of hypotheses, data were collected through quantitative methods used questionnaires to 150 customers of Purworejo Post Office. Methods of analysis used multiple linear regression analysis. Sampling technique in this study using accidental sampling.The results showed that the value of the F test was 63,139. In this study, the value of coefficient of determination showed 75,8, the model in this study were able to explain variation in the dependent variabel of 0.758 or 75.8%. The variabels of tangible, reliability, responsiveness, assurance and empathy affect the customer satisfaction Purworejo Post Office